Analisis Pengaruh Kualitas Produk, Harga, dan Kualitas Pelayanan terhadap Kepuasan Konsumen Benih Padi Produksi BPTP Balai Benih Pertanian Kabupaten Bantul - Doni Hermawan Dwi Yulianto (Hunatech Vol. XXX, No. XXX, 2022)
This study aims to analyze the effect of the product quality, the price, and the service quality towards the consumer satisfaction of the rice seeds produced by BPTP Balai Benih Pertanian (The Agricultural Technology Research Center for Seeds) Barongan. This quantitative research uses a survey method in which an investigation is carried out to obtain the facts from the existing symptoms. The determination of the location used the purposive method, a deliberate determination of the research location based on the considerations of BPTP BBP Bantul Regency, which provides excellent and qualified seeds, as well as a government institution which engages in advancing the welfare of peasants, especially in Bantul Regency. The types of data used are primary data and secondary data. The data collection techniques used are observation, interviews, and documentation, while the data analysis techniques used descriptive analysis, multiple linear regression analysis, f test, and t test. The respondents were 40 people who were selected through incidental sampling. The interpretation of the analysis results shows 95% confidence level. The results showed the significance of the effect of price on consumer satisfaction.